HUBUNGAN DURASI BEKERJA DENGAN COMPUTER VISION SYNDROME (CVS) PADA KARYAWAN PMI LENTENG AGUNG TAHUN 2021 - Ferdi Valerio (2022)
This modern generation where the world is in an era where technological revolution subconsciously changes our lifestyle. Computer usage among office workers and laboratory workers have increased along with technological advancement in the last twenty years. This phenomenon causes an increase in health problems especially in work-related health problems which is related in computer usage known as Computer Vision Syndrome. The most common symptoms occured in prolonged computer usage is eye and vision problems. The objective of this research is to determine the relations between duration and computer vision syndrome at Lenteng Agung Red Cross workers. This research type is using Qualitative Analysis (QA) and Cross-Sectional Study. The sample of this research is the workers of Lenteng Agung Red Cross who uses computer in accomplishing their job. The results shows that 57,9% of the respondents is confirmed positive in experiencing CVS while statistical analysis shows that computer usage duration does not significantly related in CVS cases.